Rice bran modulates renal disease risk factors in animals submitted to high sugar-fat diet - Siqueira, Juliana Silva [UNESP]; Francisqueti-Ferron, Fabiane Valentini [UNESP]; Garcia, Jessica Leite [UNESP]; Silva, Carol Cristina Vagula de Almeida [UNESP]; Costa, Mariane Rovero [UNESP]; Nakandakare-Maia, Erika Tiemi [UNESP]; Moreto, Fernando [UNESP]; Ferreira, Ana Lucia A. [UNESP]; Minatel, Igor Otavio [UNESP]; Togneri Ferron, Artur Junio [UNESP]; Corrêa, Camila Renata [UNESP] (Soc Brasileira Nefrologia, 2021)
Introduction: Obesity, diabetes, and hypertension are common risk factors for chronic kidney disease (CKD). CKD arises due to many pathological insults, including inflammation and oxidative stress, which affect renal function and destroy nephrons. Rice bran (RB) is rich in vitamins and minerals, and contains significant amount of antioxidants. The aim of this study was to evaluate the preventive effect of RB on renal disease risk factors. Methods: Male Wistar rats (+/- 325 g) were divided into two experimental groups to received a high sugar-fat diet (HSF, n = 8) or high sugar-fat diet with rice bran (HSF + RB, n = 8) for 20 weeks. At the end, renal function, body composition, metabolic parameters, renal inflammatory and oxidative stress markers were analyzed. Results: RB prevented obesity [AI (HSF= 9.92 +/- 1.19 vs HSF + RB= 6.62 +/- 0.78)], insulin resistance [HOMA (HSF= 83 +/- 8 vs. HSF + RB= 42 +/- 11)], dyslipidemia [TG (HSF= 167 +/- 41 vs. HSF + RB=92 +/- 40)], inflammation [TNF-a (HSF= 80 +/- 12 vs. HSF + RB=57 +/- 14), IL-6 (903 +/- 274 vs. HSF + RB=535 +/- 277)], oxidative stress [protein carbonylation (HSF= 3.38 +/- 0.18 vs. HSF + RB=2.68 +/- 0.29), RAGE (HSF=702 +/- 36 vs. RSF + RB=570 +/- 190)], and renal disease [protein/creatinine ratio (HSF=1.10 +/- 0.38 vs. HSF + RB=0.49 +/- 0.16)]. Conclusion: In conclusion, rice bran prevented renal disease by modulating risk factors.
Keywords: Kidney Function Tests; Phytochemicals; Inflammation; Oxidative Stress